The impact of Jin Shangyi's oil painting education on contemporary art pedagogy - Yaxin Peng; Junior Kimwah (Human Resource Management Academic Research Society, 2025)
Jin Shangyi is one of the important founders of Chinese oil painting education and the first generation of oil painters trained after the founding of New China. The history of Chinese oil painting is very short. Whether from the exploration of his own profession or the development of Chinese art education, Jin Shangyi advocates starting from the reality of Chinese oil painting, linking artistic creation with life, combining China's excellent traditional culture with the innovation of oil painting art, and moving forward steadily on the premise of constantly consolidating basic skills. Mr. Jin has profoundly influenced the development of Chinese oil painting education and promoted the process of nationalization of Chinese oil painting. This paper aims to explore the continued influence and value of Jin Shangyi's educational philosophy in contemporary art education, provide a model for contemporary art education to balance tradition and innovation, techniques and expression, and provide important inspiration for the growth of young artists.